An encryption algorithm based on combined chaos in body area networks. (January 2018) - Wang, Wei; Si, Miaomiao; Pang, Yu; Ran, Peng; Wang, Huiqian; Jiang, Xiaoming; Liu, Yu; Wu, Jun; Wu, Wei; Chilamkurti, Naveen; Jeon, Gwanggil
Abstract: Data encryption of sensor nodes is very important in body area networks (BANs) since the physiological data of an individual are highly sensitive. However, past encryption methods have small key space, which makes them vulnerable to attacks. In this paper, we propose a new encryption algorithm based on combined chaos. Firstly, Logistic and Kent chaotic mappings are introduced to produce two sub-matrices, and then a combined matrix is generated to perform XOR operation with the original data for encryption. The experimental results indicate that the proposed algorithm has a large key space, high key sensitivity and excellent attack resistance ability, and is feasible in privacy protection of BAN system.